Increased basal forebrain volumes could prevent cognitive decline in LRRK2 Parkinson's disease - Lucia Batzu; Daniele Urso; Michel J. Grothe; Dániel Veréb; K. Ray Chaudhuri; Joana B. Pereira (Neurobiology of Disease, 2023)
Background and objectives: It has been recently suggested that LRRK2 mutations are associated with a more benign clinical phenotype and a potentially more preserved cholinergic function in Parkinson's disease (PD). However, to our knowledge, no studies have tested whether the better clinical progression observed in LRRK2-PD patients is associated with more preserved volumes of a cholinergic brain area, the basal forebrain (BF). To address this hypothesis, here we compared BF volumes in LRRK2 carriers with and without PD with respect to idiopathic PD (iPD) patients and controls, and assessed whether they are associated with better clinical progression observed in LRRK2-PD compared to iPD. Methods: Thirty-one symptomatic LRRK2-PD patients and 13 asymptomatic LRRK2 individuals were included from the Parkinson's Progression Markers Initiative. In addition, 31 patients with iPD and 13 healthy controls matched to the previous groups were also included. BF volumes were automatically extracted from baseline T1-weighted MRI scans using a stereotactic atlas of cholinergic nuclei. These volumes were then compared between groups and their relationship with longitudinal cognitive changes was evaluated using linear mixed effects models. Mediation analyses assessed whether BF volumes mediated differences in cognitive trajectories between groups. Results: LRRK2-PD patients showed significantly higher BF volumes compared to iPD (P = 0.019) as did asymptomatic LRRK2 subjects compared to controls (P = 0.008). There were no other significant differences in cortical regions or subcortical volumes between these groups. BF volumes predicted longitudinal decline in several cognitive functions in iPD patients but not in LRRK2-PD, who did not show cognitive changes over a 4-year follow-up period. BF volumes were a significant mediator of the different cognitive trajectories between iPD and LRRK2-PD patients (95% CI 0.056–2.955). Discussion: Our findings suggest that mutations in LRRK2 are associated with increased BF volumes, potentially reflecting a compensatory hypercholinergic state that could prevent cognitive decline in LRRK2-PD patients.